Implementación de un conjunto de objetos de aprendizaje y una aplicación web de cuestionaríos dinámicos integrados en una herramienta de soporte para el autoaprendizaje de los conceptos de programación básica dirigido a estudiantes de la facultad de ingeniería en electricidad y computación - Carrasco, V. (2009)
This project demonstrates the importance of developing a web application as a tool for self-study, for students who are taking introductory programming courses offered by FIEC because as a value-added uses the Learning Objects’ methodology and related standards for its implementation. This tool provides the student the greatest amount possible examples, and feedback respectively, using the questionnaire module and code execution (compilation) to improve their skills in solving problems. The system also has a Theory module that provides the student to remember or reinforce the knowledge acquired in class. Furthermore, this tool enables for Programming teachers take decisions, based on results of exercises solved for students, which allow them to identify the topics that have greater understanding problems for students.